A Triple Helix Synergy Model for Strengthening Entrepreneurial Ecosystems in Developing Economies - Danti Astrini; Mashadi Mashadi; Mumuh Mulyana (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Entrepreneurship plays a pivotal role in Indonesia’s economic transformation, yet the national entrepreneurial ecosystem remains constrained by fragmented policies, weak university–industry linkages, and limited cross-sector collaboration. Despite the rapid growth of MSMEs, expanding digitalization, and increasing government attention to innovation, these opportunities often fail to translate into a coherent and sustainable ecosystem. This study develops the Triple Helix Synergy Model, an integrative conceptual framework that realigns the roles of government, academia, and industry through structured collaborative mechanisms reinforced by digital transformation. Using a conceptual qualitative approach supported by a thematic synthesis of 70 peer-reviewed articles (2010–2024) and major policy documents (OECD, World Bank, UNDP), the study identifies four core components shaping ecosystem performance: Inputs, Collaborative Mechanisms, Outputs, and Outcomes. Findings reveal persistent regulatory misalignment, limited applied research and commercialization pathways, weak industry absorptive capacity—particularly among MSMEs—and the absence of integrated digital collaboration platforms. The proposed model embeds regulatory alignment, innovation co-creation, resource sharing, and digital governance as essential mechanisms for strengthening ecosystem connectivity. Theoretically, this study advances Triple Helix scholarship by contextualizing it for developing economies and positioning digital transformation as a central driver of innovation governance. Practically, the model offers actionable guidance for policymakers, universities, and industry actors to enhance research commercialization, support MSME upgrading, and foster a more resilient and innovation-driven economy. Keywords: Triple Helix, entrepreneurial ecosystem, co-creation, digital platforms, MSMEs, innovation governance, government–academia–industry collaboration, developing economies.